Peer Group Embeddedness and Academic Motivation: A Developmental Perspective - Reindl, Marion (Frontiers in Psychology, 2021)
The present study focused on the increasing importance of peer group embeddedness on domain-specific academic motivation (intrinsic value and mastery goals) over the course of early adolescence. The research questions were investigated based on a five-wave longitudinal study over two school years (seventh and eighth grade) in Germany. The final sample comprised of 349 students. True-Intraindividual-Change models showed a positive effect of a change in peer group embeddedness in the first half of the eighth grade on the change of all domain-specific motivational dimensions - except for intrinsic value in English – in the second half of the eighth grade. In the seventh grade, a change of peer group embeddedness had no effect on all motivational dimensions. Results were discussed in terms of taking a developmental perspective for both peer group embeddedness and student academic motivation.